Low cost high performance concrete using low quality fly ash - Camões, Aires (1998)
High performance concretes (HPC) usually have been produced using silica fume, high quality fly ash and carefully chosen aggregates. These constituents increase drastically the initial cost of HPCs. The objectives of this research work were twofold. On one hand, it intended to study the possibility of producing low cost HPC, with 28 day strengths in the range of 65 MPa, using low quality fly ash and locally available crushed aggregates. On the other hand, to verify the impact of carbon content of fly ash on the strength and durability of HPC. For this purpose it was decided to enhance the ‘as received’ fly ash by eliminating particles coarser than 75m, thus reducing the carbon content by 50%. Compressive strength and diffusion coefficient of concretes replacing 0, 20%, 40%, and 60% of Portland cement by ‘as received’ fly ash, and 20% and 40% replacement by ‘enhanced’ fly ash, were determined. Comparing the results obtained, it was found that HPC with up to 65 MPa can be made by replacing up to 40% of cement by ‘as received’ and ‘enhanced’ fly ash and using the crushed granite aggregates. It was also observed that the carbon content did have little impact on the strength and durability of concrete. Furthermore, it was observed that the durability of concrete, as measured by diffusion coefficient, increased drastically when fly ash replaced partially Portland cement.